Natural history of Echinococcus granulosus microcyst development in long term in vitro culture and molecular and morphological changes induced by insulin and BMP-4 - Derakhshani, Ali; Mousavi, Seyed Mohammad; Rezaei, Masoud; Afgar, Ali; Keyhani, Ali Reza; Mohammadi, Mohammad Ali; Dabiri, Shahriar; Fasihi Harandi, Majid (Frontiers in Veterinary Science, 2023)
Introduction Cystic echinococcosis (CE) caused by the cestode Echinococcus granulosus is a disease of worldwide public health and economic importance. The determinants and underlying cellular mechanisms of CE development and fate in intermediate hosts are largely unknown. Hormones and cytokines such as insulin and BMP-4 are the key players in the development, differentiation, and apoptosis. In this study, we evaluated the long term natural history of E. granulosus microcysts in an vitro setting and the molecular and morphological changes induced by the growth factors, insulin and BMP4 during the development of metacestode stage of E. granulosus. Methods E. granulosus protoscoleces were cultivated and the parasite development was followed in the long term mono-phasic culture for 105 days and the morphometric, molecular and immunohistochemical changes were evaluated, including the microcysts number and size, microcysts development and deformation rates as well as the markers of calcification (Alizarin Red staining) and apoptosis (BAX, BCL2, Caspase-3, Caspase-8 and TNF-α expression) in the microcysts. Also the biological, histological and molecular consequences of insulin and BMP-4 treatment on the parasite development were evaluated. Results Insulin and BMP-4 treatment of microcysts resulted in significant increase in microcyst formation, increased size, reduced apoptosis and deformation of the microcysts. Alizarin red staining of the microcysts treated with the insulin and BMP-4 confirmed that calcium deposition is significantly lower than the untreated microcysts. Also Alizarin Red staining and Immunohistochemistry of the microcysts indicates that calcium accumulation in deformed microcysts is higher than the normal ones on day 105. The microcysts began to wrinkle and the germinal layer was partially detached from the laminated layer on day 84. Conclusion Results of the present study suggest that the degenerative changes in hydatid cysts can be slowed down by insulin and BMP-4, indicating that cellular factors and host hormones could contribute to the longevity of hydatid cysts. Significant evidences are provided suggesting that the microcysts cultivated in vitro can undergo calcification and apoptotic processes similar to what have been observed in the natural hydatid infection in the intermediate hosts.